Pure Red Cell Aplasia with Adult Onset Still’s Disease - Nicholas Robillard; Paul Van Nguyen; Robert Wistaff; Mikhael Laskine (Case Reports in Medicine)
Adult Onset Still’s Disease (AOSD) is a rare inflammatory syndrome mostly seen in young adults. Known for its wide range of clinical manifestations, AOSD often presents with nonremitting systemic signs and symptoms. Many rare case associations have been described with AOSD, but only few with pure red cell aplasia (PRCA). We are presenting a fourth known case of a young female adult with AOSD and PRCA in the literature.